2015
DOI: 10.5812/archcid.10(2)2015.27432
|View full text |Cite
|
Sign up to set email alerts
|

Serological Diagnosis of Helicobacter pylori Infection in Patients With a Polycystic Ovary Syndrome

Abstract: Background: Polycystic Ovary Syndrome (PCOS) is the most common endocrine disorder in 4% -6% of women in the reproductive age and is a common cause of infertility. Even though the number of investigations is scarce, studies show that Helicobacter pylori infection may influence reproduction. Objectives: The purpose of this study was to determine and compare the levels of H. pylori specific antibodies IgA, IgG and anti-CagA at both PCOS and non-PCOS women with their spouses using the serological test. Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…study. Similarly to our study, another study involving 254 individuals (127 with PCOS and 127 without PCOS) did not find significantly higher positive titers of antibodies to H. pylori including IgA, IgG and CagA in the PCOS group compared with control group . In that study, higher rates of autoantibodies to H. pylori including IgA, IgG, CagA were seen in both patients with PCOS and those without PCOS (35%, 62%, 60.5%; 30%, 60%, 39.5%; P > 0.05).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…study. Similarly to our study, another study involving 254 individuals (127 with PCOS and 127 without PCOS) did not find significantly higher positive titers of antibodies to H. pylori including IgA, IgG and CagA in the PCOS group compared with control group . In that study, higher rates of autoantibodies to H. pylori including IgA, IgG, CagA were seen in both patients with PCOS and those without PCOS (35%, 62%, 60.5%; 30%, 60%, 39.5%; P > 0.05).…”
Section: Discussionsupporting
confidence: 83%
“…32 It is possible that non-PCOS AYA patients with H. pylori infection may develop PCOS in the future, similarly to the time required for carcinogenesis to occur in H. pylori patients with chronic gastritis and peptic ulcer. 33 34 In that study, higher rates of autoantibodies to H. pylori including IgA, IgG, CagA were seen in both patients with PCOS and those without PCOS (35%, 62%, 60.5%; 30%, 60%, 39.5%; P > 0.05). Therefore, given that the subjects in that study (and therefore that region) seem to have a high prevalence of H. pylori infection, more studies involving a large number of participants are needed to clarify a possible link between H. pylori infection and PCOS.…”
Section: Discussionmentioning
confidence: 77%
“…A total of 1,902 participants were enrolled, including 626 patients and 1,276 controls. In total, 503 women diagnosed with polycystic ovary syndrome (PCOS) were cases in three articles [15][16][17]; other women (n = 124) had no PCOS. The design of all included studies was a case-control study.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…All the included studies detected H. pylori IgG antibodies in serum to diagnose H. pylori infection. Three articles found no association between H. pylori and infertility via serologic examination [16][17][18]; however, the other studies found that H. pylori was a risk factor for infertility [15,17,19]. Table 2 shows the level of evidence provided according to the NOS criteria.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation